2023
DOI: 10.1021/acs.macromol.2c02547
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Covalent Bond Exchange Enhances Penetrant Diffusion in Dense Vitrimers

Abstract: Polymer membranes are commonly pursued for passive separations, which require less energy than distillation. Typically, glassy materials are chosen for gas separations due to extreme sensitivity to size differences in penetrants, whereas rubbers are used for liquid separations due to solubility differences. Vitrimers, dynamic polymer networks with associative bond exchange, are an emerging class of polymers that have gained much attention as self-healing and recyclable materials. Here, in a new direction for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Networks with C 6 diol (50 mg, 2 equiv) and a fast boronic acid cross-linker (1 equiv) were prepared by the same procedure as discussed above, and a stoichiometric ratio of alcohol and acid groups was maintained. The difference in exchange kinetics is a factor of ∼10,000 as reported in prior work on small molecules and vitrimers. , The term precise only refers to the carbon spacing, not the network topology. Fourier transform infrared spectroscopy (FTIR, Figure S9) of the networks was performed at 80 °C to confirm the absence of the broad OH peak in the 3000 to 3500 cm –1 range corresponding to unreacted species of the diols and boric acid.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…Networks with C 6 diol (50 mg, 2 equiv) and a fast boronic acid cross-linker (1 equiv) were prepared by the same procedure as discussed above, and a stoichiometric ratio of alcohol and acid groups was maintained. The difference in exchange kinetics is a factor of ∼10,000 as reported in prior work on small molecules and vitrimers. , The term precise only refers to the carbon spacing, not the network topology. Fourier transform infrared spectroscopy (FTIR, Figure S9) of the networks was performed at 80 °C to confirm the absence of the broad OH peak in the 3000 to 3500 cm –1 range corresponding to unreacted species of the diols and boric acid.…”
mentioning
confidence: 79%
“…Recently, we demonstrated that vitrimers with fast exchanging dynamic bonds can greatly enhance the diffusion of a large aromatic dye relative to a permanent network with the same chemistry and volumetric cross-link density. 43 Model butyl acrylate networks with boronic ester cross-links were synthesized over a broad range of cross-link densities with either fast or slow bond exchange relative to the probe hopping time. If the characteristic exchange time is within an order of magnitude of the diffusive hopping time (determined from the experimentally measured diffusion coefficient), then the exchange process facilitates probe motion.…”
mentioning
confidence: 99%
See 3 more Smart Citations